Image Representation in Supporting Students' Vocabulary Comprehension in Textbooks: A Roland Barthes Semiotic Analysis - Hilmalia Asyifa; Syihabuddin Syihabuddin (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
Vocabulary mastery is crucial for developing students' Arabic language skills at the MTs level. Images in textbooks can help students understand vocabulary by connecting it to real life situations. However, images are often merely supplementary, leading to their educational value being overlooked. This study aims to analyze the appropriateness of images and their meanings using Roland Barthes' semiotic theory to support students' vocabulary comprehension. This study employs a qualitative approach, utilizing content analysis and purposive sampling techniques on images from the 2020 Ministry of Religious Affairs published Arabic textbook for eighth grade MTs students. Data were collected through document analysis, open ended questionnaires administered to eighth grade students at MTsS Al-Musyawarah Lembang, and interviews with teachers. The results indicate that the images in the textbook generally align with students' daily lives. However, Roland Barthes's semiotic analysis identified several issues, such as gender stereotypes, gender bias in grammar, and cultural localization. These issues create a psychological effect known as the "superiority of images," meaning students trust the images more than the Arabic text provided. Therefore, the images need to be periodically revised to prevent long term memory errors in students. Teachers also need to play an active role in correcting students' understanding in the classroom.